2008
DOI: 10.1371/journal.pone.0002002
|View full text |Cite
|
Sign up to set email alerts
|

Damaged DNA Binding Protein 2 Plays a Role in Breast Cancer Cell Growth

Abstract: The Damaged DNA binding protein 2 (DDB2), is involved in nucleotide excision repair as well as in other biological processes in normal cells, including transcription and cell cycle regulation. Loss of DDB2 function may be related to tumor susceptibility. However, hypothesis of this study was that DDB2 could play a role in breast cancer cell growth, resulting in its well known interaction with the proliferative marker E2F1 in breast neoplasia. DDB2 gene was overexpressed in estrogen receptor (ER)-positive (MCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…We observed previously that DDB2 expression was inversely correlated with the invasive properties of breast tumor cells, and that a constitutive overexpression of DDB2 in nonmetastatic cells induced cell proliferation by activating the G 1 -S transition phase of the cell cycle (2). In the present study, our findings summarized in Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We observed previously that DDB2 expression was inversely correlated with the invasive properties of breast tumor cells, and that a constitutive overexpression of DDB2 in nonmetastatic cells induced cell proliferation by activating the G 1 -S transition phase of the cell cycle (2). In the present study, our findings summarized in Fig.…”
Section: Discussionsupporting
confidence: 76%
“…DDB2 is overexpressed in nonmetastatic breast tumor cells and plays a role in their proliferation by favoring G 1 -S transition entry and their progression through the S-phase of the cell cycle (2). We reported that DDB2 stimulates the proliferation of nonmetastatic breast tumor cells, at least in part by maintaining a low basal expression of mitochondrial superoxide dismutase (MnSOD) through its binding to a specific and well-characterized DNA sequence in the proximal promoter of the MnSOD gene (3).…”
Section: Introductionmentioning
confidence: 99%
“…Expression Vector, RNA Interference, RNA Antisense, and Stable Transfection-The DDB2 pcDNA3(ϩ) expression vector, the pSIREN/U6/DDB2-siRNA vector, and the pcDNA vector containing antisense cDNA of human MnSOD were constructed and used for stable transfection of breast cancer and COS-7 cells, as described elsewhere (14,18).…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences (Invitrogen) and the expected product sizes of SOD2, DDB1, DDB2, MDR1, and ␤-actin are detailed in Table 1. PCR analysis was carried out, as described previously (14,18). Ethidium bromide-stained bands resulting from the amplification were visualized by UV transillumination, and the fluorescence intensity was quantified using a Gel Doc 2000 system (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation